System productivity of wheat- sesame-t. Aman rice cropping pattern as influenced by varietal replacement (Bangladesh Agronomy Journal, 2019)
The study was carried out at Multi Location Testing site, Sujanagar, Pabna during two consecutive years of 2011-12 and 2012-13 growing season to assess the performance of the pattern with newly released crop varieties against the existing one usually practiced by the farmers with traditional varieties in order to increase yield and economic return. The experiment was laid out in a randomized complete block design with six dispersed replications at farmer’s field. In improved pattern (IP) BARI Gom-26, BARI Til-4 and Binadhan-7 variety were used for wheat, sesame and T. aman rice, respectively. On the contrary in existing pattern (EP) farmers usually use BARI Gom-21, local (char shira) and Sharna cultivar for wheat, sesame and T. aman rice, respectively. The mean yield was recorded 4.66, 1.34 and 4.79 t ha-1 from wheat (BARI Gom-26), sesame (BARI Til-4) and T. aman (Binadhan-7) respectively from the improved cropping pattern whereas average yield 3.81, 0.98 and 4.58 t ha-1 was obtained from wheat (BARI Gom-21), sesame (local) and T. aman (Sharna), respectively from the existing pattern. Two years mean data also showed that improved pattern provided about 18% higher REY compared to existing pattern. Sustainable yield index and production efficiency were also found maximum with improved cropping pattern. Similarly, maximum gross margin and benefit cost ratio were obtained from improved cropping pattern.Bangladesh Agron. J. 2018, 21(2): 13-18